Analyzing bit error rate of relay sensors selection in wireless cooperative communication systems - Ahmed Allawy Alawady; Ahmed Alkhayyat; Mohammed Ahmed Jubair; Mustafa Hamid Hassan; Salama A. Mostafa (Institute of Advanced Engineering and Science, 2021)
Cooperative communication systems, which make use of the intermediate relays between the transmitter and the receiver, have been employed as an effective technique to combat the channel fading and to enhance system performance. Cooperative systems have some drawbacks such as high latency and may diversity order not guaranteed. To alleviate the negative effects of these factors, the relay selection protocol is employed in cooperative communication systems to increase overall cooperative system performance. Relay selection in the cooperative systems enables the source to cooperate with the single relay node rather than multiple relay nodes which guaranteed the diversity order.